MERIT OR DEMERIT OF BILINGUALITY IN LEARNING ENGLISH AS A FOREIGN LANGUAGE? - Mojtaba Maghsudi (Soegijapranata Catholic University, 2010)
In surveys of third language acquisition (L3A) research, mixed results and findings demonstrate that there is no consensus among the researchers regarding the advantages and/or disadvantages ofbilinguality on L3A. The main concern of the present study was, thus, to probe the probable differences between Iranian bilingual/monolingual learners of English regarding their syntactic knowledge. It was an attempt to investigate whether bilingual and monolingual learners of English differ significantly in learning embedded question, preposition stranding and pied piping knowledge. To carry out this study, a total of399 male andfemale subjects at seven preuniversity centers in Arak, Iran were randomly selected from among two groups of Turkish-Persian bilinguals and Persian monolinguals. A general English proficiency test, a questionnaire, and a syntactic structure test were administered to both groups. Statistical analyses including ANOVA, t-test and descriptive statistics revealed the following outcomes: 1- Monolingual and bilingual learners did not differ in acquiring syntactic structure, 2- No significant difference was observed between gender of monolinguals and bilinguals' performances in acquiring syntactic structure.